SEASONAL VARIABILITY OF LIGHT ABSORPTION COEFFICIENT OF SURFACE WATER - Bisman Nababan; Denny A. Wiguna; Risti E. Arhatin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Absorption coefficient measurement can be used in estimating water quality, optical characteristic of water column, and marine bio-optical models. The purposes of this research were to determine values and variability of sea surface absorption coefficient in the northeastern Gulf of Mexico (NEGOM) based on various seasons. The data were collected in spring, summer, and fall seasons in 1999-2000 with AC-9 instrument. The spatial distribution of absorption coefficient showed that relatively high values were generally found along the run off Missisippi, Mobile, Chochawati, Escambia, Apalachicola, and Suwannee rivers, as well as Tampa Bay. Meanwhile, relatively low values were found in offshore region. This pattern followed the distribution pattern of chlorophyll and CDOM. Based on the local region comparison of spectral average value of absorption coefficient, we found a significant difference (α = 95%) among regions with the highest value in the run off of the Mississippi and Mobile rivers, and the lowest value in the offshore region. Comparison of spectral average value of absorption coefficient among seasons at the three primary wavelengths (blue=440 nm, green=510 nm, and red=676 nm) also showed a significant difference (α = 95%) with the highest value during the summer 1999 (Su-99) and the lowest value during the spring of 2000 (Sp-00). Absorption coefficient values were influenced by oceanographic factors that varied in every season such as wind, surface currents, upwelling, the location and speed of the Loop Current, and the river discharge of fresh water into the NEGOM.Keywords: absorption coefficient, seasons, chlorophyll, CDOM, northeastern Gulf of Mexico